Be Information Literate: The Ghana Institute of Journalism Employees’ Experience - Nyantakyi-Baah, Lydia; Afachao, Ernest; Abrokwah, Stella (Ghana Library Journal, 2016)
The purpose of the study is to explore the relationship between information literacy and the workplace. The study also aims to have a better understanding of information literacy skills of GIJ staff and it influence on their work performance. The study population consisted of the registry staff of the Ghana Institute of Journalism. A questionnaire was developed to collect data from respondents. The study found that poor Internet connectivity at the workplace coupled with staff’s lack of information literacy skills and inadequate print materials were challenges affecting the effective delivery and experience of information literacy at the Ghana Institute of Journalism. Some workers expressed confidence in using information to accomplish task at the workplace. However, ten (10) or 33% of the respondents said they always have the confidence and felt competent, to evaluate information and their sources. It is hoped that the findings will inform both management and librarians at the Ghana Institute of Journalism to equip the Institute’s information centres with the necessary information resources and also plan effective information literacy programmes for staff of the Institute to enhance performance of task at the workplace.